SISTEM PERTAHANAN JEPANG DI JAWA Studi Berdasarkan Tinggalan Gua Jepang Di Banyumas, Jawa Tengah - Muhammad Chawari (Berkala Arkeologi, 2013)
Towards mid of 20th century Indonesia was not yet fully freed from suffering, particularly the Japanese occupation. During the period of 3 years, from 1942 to 1945 Japan seized Indonesia. First they landed in is East Kalimantan. From here they occupied the entire archipelago. To defend the territory, the built numerous fortress called bunker. The term often used to refer to Japanese Caves. Japanese bunker and Japanese caves are different. Bunkers were made of a mixture of cement, stone, and sand, while the cave were made by drilling holes in the hills horizontally, the entire Japanese defense system in Banyumas are caves. By observing Japanese caves, particularly in Banyumas, we can learn about the defense system elaborated by the Japanese in Java during their occupation.